Transformasi Guru Mengungkap Perkembangan Metakognitif Positif dalam Berbicara Anak Pada Kelas II Sekolah Dasar - Susanti, Dinik (Fakultas Ilmu Pendidikan Universitas Negeri Padang, 2024)
The formulation of the research problem is to determine the development of metacognitive knowledge in speaking in second grade elementary school students. The development of metacognitive knowledge that we want to observe is the use of effective speaking strategies with better language quality. The research uses a qualitative descriptive approach. Data collection includes observation, interviews, and content analysis. The research stages used case studies with several teachers and students as research subjects. The research results show that with the right approach and application of good methods, positive metacognitive development in elementary school children's speaking can increase significantly. The teacher's role is very important in changing the way children think about language and speech. This research found that children who were encouraged to think metacognitively and use effective speaking strategies had better language quality. Teacher transformation plays a central role in revealing positive metacognitive development in elementary school students' speaking.